Incidence, predictors and clinical implications of new renal impairment following percutaneous coronary intervention - Danny Liew; Christopher M Reid; Dion Stub; James A Shaw; Angela Brennan; Diem T Dinh; Stephen J Duffy; Jamie Layland; William Chan; William J van Gaal; Nathan Wong; Riley Batchelor (Open Heart, 2022)
Background Renal impairment post-percutaneous coronary intervention (post-PCI) is a well-described adverse effect following the administration of contrast media. Within a large cohort of registry patients, we aimed to explore the incidence, predictors and clinical outcomes of renal impairment post-PCI.Methods The Victorian Cardiac Outcomes Registry is an Australian state-based clinical quality registry focusing on collecting data from all PCI capable centres. Data from 36 970 consecutive PCI cases performed between 2014 and 2018 were analysed. Patients were separated into three groups based on post-procedure creatinine levels (new renal impairment (NRI), defined as an absolute rise in serum creatinine>44.2 µmol/L or>25% of baseline creatinine; new renal impairment requiring dialysis (NDR), defined as worsening renal failure that necessitated a new requirement for renal dialysis; no NRI). Multivariate logistic regression analysis was performed to investigate the impact of NRI and NDR on clinical outcomes.Results 3.1% (n=1134) of patients developed NRI, with an additional 0.6% (n=225) requiring dialysis. 96.3% (n=35 611) of patients did not develop NRI. Those who developed renal impairment were more comorbid, with higher rates of diabetes (22% vs 38% vs 38%, p<0.001), peripheral vascular disease (3.4% vs 8.2% vs 11%, p<0.001), chronic kidney disease (19% vs 49.7% vs 54.2%) and severe left ventricular dysfunction (5% vs 22% vs 40%, p<0.001). Multivariable analysis found that when compared with the no NRI group, those in the combined NRI/NDR group were at a greater risk of 30-day mortality (OR 4.77; 95% CI 3.89 to 5.86, p<0.001) and 30-day major adverse cardiac events (OR 3.72; 95% CI 3.15 to 4.39, p<0.001).Conclusions NRI post-PCI remains a common occurrence, especially among comorbid patients, and is associated with a significantly increased morbidity and mortality risk.